The construction of human–animal relations: National Jumps Day 2013 at Te Rapa, Hamilton, New Zealand. (December 2014) - McManus, Phil; Graham, Raewyn; Ruse, Karen
Abstract New Zealand is an important place for thoroughbred breeding and racing. Most races are on the flat, but jumps racing is conducted in the cooler months. The 2013 National Jumps Day at Te Rapa, Hamilton, was a significant space for the construction of human–animal relations. Drawing on three bodies of accounts, we ask whether social media contributes to the realignment of perspectives or reinforces existing human–animal relations. We explore competing narratives and demonstrate how animals, people, activities and places are constructed, including making animal deaths unrecognisable to perpetuate activities that are questioned by contemporary animal geographies.